Reconstructing a Junior High School English Question Bank through Qualitative Item Analysis and Higher-Order Thinking Skills Integration - Tedi Rohadi; Jamaludin; Nana Priajana; Shofia Mardhiyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Assessment plays an important role in supporting learning and evaluating students’ cognitive development. However, many classroom assessments still emphasize lower-order thinking skills and contain weaknesses in item construction. This study aimed to analyze the shortcomings of existing English question banks and reconstruct them into a more cognitively balanced assessment instrument for junior high school learning. The study employed a qualitative design using document analysis of sixty multiple-choice items taken from two English question banks. The items were analyzed based on Bloom’s Revised Taxonomy and item-writing guidelines focusing on cognitive levels and item construction. The results showed that the existing question banks were dominated by lower-order thinking skills, particularly at the applying level, while higher-order thinking skills were rarely represented. Several structural weaknesses were also identified, including implausible distractors, heterogeneous options, and unclear stems. Based on these findings, the question bank was reconstructed by redistributing cognitive levels and improving item construction. The reconstructed items were also prepared for digital implementation using the Quizziz platform to support formative assessment. The study concludes that systematic item analysis can improve both the cognitive quality and structural validity of assessment instruments. The reconstructed question bank provides a more balanced and effective assessment tool for junior high school English learning.